2020
DOI: 10.1079/ac.66265.20203483350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rotation farming of rice and shrimp in the Mekong Delta, Vietnam.

Abstract: Rotation farming of rice and shrimp is a typical farming system in the Mekong Delta of Vietnam, where saline water intrusion takes place seasonally. In this area, shrimp (Penaeus monodon) culture is carried out during the dry season and rice is cultivated during the rainy season. The growth, survival rate, water quality variation and cost: benefit ratio of the system were monitored in three experimental shrimp farms (1-1.3 ha per pond) in Soc Trang province and three others (0.4-0.5 ha per pond) in Bac Lieu pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Some women may have been reluctant in participating in the learning-by-doing phase, but many complained about the fact that they were mostly assigned the reproductive tasks during the practical on-farm demonstrations, fetching water and cooking food, so that they were not able to focus on the real training in the field. Time constraints generally faced by women because of their reproductive activities may also have prevented them to fully participate in the practical on-farm demonstration trainings (Kinkingninhoun Medagbe et al, 2020;Truong and Yamada, 2002). In addition, male farmers were found to have a better understanding of the trainings' contents than female farmers due to their higher level of formal education or schooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some women may have been reluctant in participating in the learning-by-doing phase, but many complained about the fact that they were mostly assigned the reproductive tasks during the practical on-farm demonstrations, fetching water and cooking food, so that they were not able to focus on the real training in the field. Time constraints generally faced by women because of their reproductive activities may also have prevented them to fully participate in the practical on-farm demonstration trainings (Kinkingninhoun Medagbe et al, 2020;Truong and Yamada, 2002). In addition, male farmers were found to have a better understanding of the trainings' contents than female farmers due to their higher level of formal education or schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Complex and gender-biased technologies are specifically affected (Hörner et al, 2022). The non-consideration of gender issues in the development and dissemination of agricultural technologies (Addison et al, 2019), the lack of female extension agents (Lugman et al, 2018;Ragasa et al, 2013), time constraints faced by women compared to men (Kinkingninhoun Medagbe et al, 2020;Samee et al, 2015;Truong and Yamada, 2002), extension agents mainly talking to male farmers and household heads, who are mostly men (Agboh-Noameshie et al, 2013;Lamontagne-Godwin et al, 2018;Theriault et al, 2017;World Bank and IFPRI, 2010) are the main factors restricting women's access to extension services. Gender inequalities in access to technologies contribute to global hunger and food insecurity (Njuki et al, 2016;World Bank, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…"Migration is a highly selective process and strongly affected by household and commune characteristics" is also confirmed by (Phuong et al, 2008, p. 2). Younger ages (from 15 to 25) and more highly educated groups were also found to significantly influence migratory behaviour (Truong Huy, 2009) Positive emotional impact of advanced transport and communication technologies…”
Section: Positive Emotional Impacts Associated With Financial Satisfa...mentioning
confidence: 99%
“…Along with ICT, the role of agricultural engineering is also important in the support and growth of the agricultural industry. Research conducted by Truong [106] to study the use of technology by rice farmers in Vietnam reported a positive impact of advanced technology and equipment on rice production in the Mekong Delta region of Vietnam. The study of Truong [106] suggested some technologies that are beneficial for both farm owners, as well as for the agricultural industry as a whole.…”
Section: Technologymentioning
confidence: 99%
“…Research conducted by Truong [106] to study the use of technology by rice farmers in Vietnam reported a positive impact of advanced technology and equipment on rice production in the Mekong Delta region of Vietnam. The study of Truong [106] suggested some technologies that are beneficial for both farm owners, as well as for the agricultural industry as a whole. Those technologies, such as row seeding, integrated pest management (IPM), "three reductions-three gains", rice dryers, and harvesting machines, are reported to increase farm yields.…”
Section: Technologymentioning
confidence: 99%